PENGARUH VARIASI LAMA PENYULINGAN DAN KECEPATAN PENGADUKAN TERHADAP MUTU MINYAK ATSIRI SEREH WANGI - SITI AISYAH (LP2MTBM MAKARIOZ, 2023)
Essential oils are oils that are volatile, odorless, fragrant and not easily decomposed at room temperature, found in various parts of plants. Essential oils contain a variety of different chemical components, but these components can be classified into four major groups that dominantly determine the properties of essential oils. Citronella essential oil is often also referred to as citronellal oil because citronella essential oil is an oil extracted by the method of steam distillation or distillation from the leaves. This study aims to determine variations in distillation time and stirring speed on the quality of citronella essential oil. The results showed that the longer the distillation time and the higher the stirring speed, the greater the yield of citronella essential oil produced. This is because the longer the heating time, the more heat will be received by the material, so that the material will evaporate the oil components present in the material so that more steam will come out of the oil components in the tissue contained in the material and The extracted oil will increase. The specific gravity produced is also in accordance with SNI, which is worth 0.850 – 0.892, where the longer the distillation process and the greater the stirring speed, the greater the specific gravity of citronella essential oil. This is because the citronella leaves will polymerize so that the purity of the oil will decrease due to the formation of polymers with higher molecular weights. Likewise, the refractive index of citronella essential oil produced is also in accordance with SNI, which ranges from 1.454 to 1.473, although the S3T3 treatment produces a refractive index that is still not in accordance with SNI, namely only 1.449. This is because the S3T3 treatment with a longer distillation time and a stirring speed that is too large will cause the resulting index of refraction to be smaller, because the longer the distillation process, the lower the density of the oil so that the refractive rays will be closer to the normal line, then the angle of refraction will be greater as a result the index of refraction will be smaller.